Assessment of Inventory Management Practices at the Ethiopian Pharmaceuticals Supply Agency, Addis Ababa, Ethiopia - Boche B; Mulugeta T; Gudeta T (Dove Medical Press, 2020)
Bekele Boche, Tidenek Mulugeta, Tadesse Gudeta Department of Social and Administrative Pharmacy, School of Pharmacy, Faculty of Health Sciences, Jimma University, Jimma, Oromia, EthiopiaCorrespondence: Tidenek Mulugeta Email tidenek11@gmail.comBackground: Maintaining an adequate level of inventory is critical since an enormous amount of capital tied up with it. Having excess inventory leads to wastage. On the contrary, insufficient commodity leads to stock out. Hence, this study aimed to assess inventory management practices of program commodities at Ethiopian Pharmaceutical Supply Agency.Methods: A descriptive cross-sectional study complemented with a qualitative method was conducted from February 21 to April 20/2019. Order fill rate, wastage rate, frequency of emergency order, acceptable storage condition met, and stock out were the metrics we used to measure the inventory management practices of the agency. Quantitative data were collected through physical observation of the warehouses and review of logistics management tools. Seventeen in-depth interviews were conducted to explore the challenges of inventory management.Results: From the total 70 program commodities managed by the agency, 2.1% wasted due to expiration and damage. These resulted in a loss of over US $2 million. The highest wastage was recorded for antimalarials which accounted for 13.1% of the malaria commodities’ total inventory value. Only 14.8% of the orders were fulfilled above 80%. Thirty-seven items were stock out on average for 8.5 average days. Longer duration of stock out (260 days) was recorded for TB commodities. Seventeen items from different programs were purchased through emergency orders with a higher frequency of levonorgestrel purchase. Only 6 (60%) warehouses met acceptable storage conditions. Space deficit, outdated warehouse designs, shortage of warehouse equipment, lack of precise data, and capacity building gaps were the inventory management challenges identified.Conclusion: Though the wastage rate was near to the acceptable range, there were lesser order fill rates, storage condition inadequacy, and significant stock-outs of program commodities. The finding implies the need for an improvement in inventory management practice of the agency.Keywords: program commodities, EPSA, inventory management